Is the Size of Insulinoma Predictive for its Endocrine Behavior? An Endoscopic Ultrasound Study - Adelmeyer, Jan; Göbel, Franziska; Kann, Peter Herbert (Experimental and Clinical Endocrinology & Diabetes, 2022)
Objective Insulinoma is a rare tumor of the pancreas that can lead to spontaneous hypoglycemia due to excessive insulin secretion. Seventy-two-hour fast is the gold standard for finding the correct diagnosis. Endoscopic ultrasound (EUS) is an established examination method to identify the suspicious lesion. Previous studies correlate the measured size of insulinoma and their endocrine behavior. This study was designed to find a relation between these variables.Methods We took the data of patients who had a histologically confirmed insulinoma after receiving an endoscopic ultrasound in our department. Size and echogenicity were correlated with the endpoint of the 72-hour fast and hormone levels.Results A total of 45 patients were identified. Most insulinomas were small with a volume of<2 cm3 (median 1.15 cm3). There was no correlation between the duration of fasting, hormone levels, and the size of the insulinoma. In addition, in a subgroup analysis, no connection could be established between the size of the insulinoma and the amount of insulin released after oral glucose exposure. We found that homogeneous tumors were significantly smaller and had a lower Ki-67 index. Furthermore, there was a tendency towards a shorter duration for the 72-hour fast for the small tumors.Discussion This data suggests that the measured size of insulinoma by EUS is not related to the time until termination of the 72-hour fast and measured hormone levels. The echogenicity seems more important, showing that homogenous tumors are an indicator of a higher differentiation, which can result in a shorter duration of the fasting period. The differences in the secretion behavior of the insulinomas could complicate the correlation of size and the 72-hour fast period.
Keywords: insulinoma; insulin; endoscopic ultrasound; imaging; 72-hour fast; hypoglycemia; tumor size